2005
DOI: 10.1562/2005-05-25-ra-541
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Effects on Protein Structural Changes and Interdomain Interactions in the Blue‐light Sensing LOV Protein YtvA

Abstract: Mutagenesis studies on the phototropin-related protein YtvA from Bacillus subtilis have revealed the role of selected structural elements in interdomain communication. The LOV (light, oxygen, voltage) domain of YtvA undergoes light-driven reactions similar to that of phot-LOV, with reversible formation of a covalent flavin-cysteine adduct. The mutated proteins Ytva-E105L and YtvA-E56Q have been studied by UV fluorescence and circular dichroism (CD) spectroscopy. E105 (L in phototropin) is located at the solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 51 publications
7
40
1
Order By: Relevance
“…Consistent with the results presented here, mutational analysis has shown that the LOV-surface salt bridge of YtvA does not appreciably contribute to the overall secondary structure of the full-length sensor protein (33). Moreover, chromophore binding is not impaired upon disruption of the LOV-surface salt bridge in full-length YtvA (33). Yet, our mutational analysis with the isolated LOV2 of Arabidopsis phot1 domain clearly indicates that disruption of the Glu-Lys salt bridge results in an almost complete loss of chromophore binding without compromising protein secondary structure (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the results presented here, mutational analysis has shown that the LOV-surface salt bridge of YtvA does not appreciably contribute to the overall secondary structure of the full-length sensor protein (33). Moreover, chromophore binding is not impaired upon disruption of the LOV-surface salt bridge in full-length YtvA (33). Yet, our mutational analysis with the isolated LOV2 of Arabidopsis phot1 domain clearly indicates that disruption of the Glu-Lys salt bridge results in an almost complete loss of chromophore binding without compromising protein secondary structure (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…3). Consistent with the results presented here, mutational analysis has shown that the LOV-surface salt bridge of YtvA does not appreciably contribute to the overall secondary structure of the full-length sensor protein (33). Moreover, chromophore binding is not impaired upon disruption of the LOV-surface salt bridge in full-length YtvA (33).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This salt bridge is located in the region of YtvA-LOV undergoing the most pronounced light-induced structural change (7), although the two residues themselves show only minor rearrangements. Disruption of the salt bridge in the E56Q mutant slows down the dark state recovery rate in vitro by a factor of 2 (39). However, in vivo, this mutant shows a similar extent of light activation of B as the wild type ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…25 LOV-domain b-sheet rearrangement also appears to be required for interdomain interactions in the bacterial photosensor YtvA from Bacillus subtilis. 26 Further studies will determine whether a signal transmission mechanism involving the central b-sheet is common to other LOV-sensor proteins. Interestingly, molecular dynamic simulations indicate that the consequences of LOV1 photoexcitation differ to that of LOV2 and involve stabilizing a conserved surface salt bridge.…”
Section: Lov2 Signal Transmissionmentioning
confidence: 99%